LITERASI IKLAN ROKOK DAN PERILAKU KONSUMTIF REMAJA MELALUI PEMBERDAYAAN REMAJA MASJID - Rika Lusri Virga (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Cigarette advertisements in broadcast media such as television and radio always associate cigarettes with a cool, confident, adventurous, loyal and macho image resulting in consumptive behavior. This research looks at how literacy of cigarette advertisement is done through empowering youth of mosque in preventing consumptive behavior. The research method used Focus Groups Discussion (FGD). The results show that the teenagers of Al-Islah mosque realize that the ads they see through television and print media are cigarette advertisements even though the display of the ad does not show the form of cigarettes and what the effects of the advertisement and the effects of smoking. The youth of the mosque also understands the content of advertising as a text that gives ideas into the culture and life of each individual as it is only in the image of a person based on the brand of cigarettes consumed. The desire to consume cigarettes is not only based on knowledge of cigarettes, but a desire that arises from his psychic cigarette consumption is caused by his acceptance in his environment.